Calreticulin exposure correlates with robust adaptive antitumor immunity and favorable prognosis in ovarian carcinoma patients - Kasikova, Lenka; Hensler, Michal; Truxova, Iva; Skapa, Petr; Laco, Jan; Belicova, Lucie; Praznovec, Ivan; Vosahlikova, Sarka; Halaska, Michael J; Brtnicky, Tomas; Rob, Lukas; Presl, Jiri; et al. (Journal for immunotherapy of cancer, 2019)
BACKGROUND: Adjuvanticity, which is the ability of neoplastic cells to deliver danger signals, is critical for the host immune system to mount spontaneous and therapy-driven anticancer immune responses. One of such signals, i.e., the exposure of calreticulin (CALR) on the membrane of malignant cells experiencing endoplasmic reticulum (ER) stress, is well known for its role in the activation of immune responses to dying cancer cells. However, the potential impact of CALR on the immune contexture of primary and metastatic high-grade serous carcinomas (HGSCs) and its prognostic value for patients with HGSC remains unclear. METHOD: We harnessed a retrospective cohort of primary (no = 152) and metastatic (no = 74) tumor samples from HGSC patients to investigate the CALR expression in relation with prognosis and function orientation of the tumor microenvironment. IHC data were complemented with transcriptomic and functional studies on second prospective cohort of freshly resected HGSC samples. In silico analysis of publicly available RNA expression data from 302 HGSC samples was used as a confirmatory approach. RESULTS: We demonstrate that CALR exposure on the surface of primary and metastatic HGSC cells is driven by a chemotherapy-independent ER stress response and culminates with the establishment of a local immune contexture characterized by TH1 polarization and cytotoxic activity that enables superior clinical benefits. CONCLUSIONS: Our data indicate that CALR levels in primary and metastatic HGSC samples have robust prognostic value linked to the activation of clinically-relevant innate and adaptive anticancer immune responses.
Keywords: nádorové mikroprostředí; CD20; Ovarian Neoplasms; prognóza; DC-LAMP; Adult; kalretikulin; Aged; dospělí; senioři; sekvenování transkriptomu; nádory vaječníků; Calreticulin; RNA-Seq; stres endoplazmatického retikula; senioři nad 80 let; lidé; ženské pohlaví; Humans; B cells; Aged, 80 and over; Prognosis; Endoplasmic Reticulum Stress; Dendritic cells; Immunogenic cell death; Cancer immunotherapy; Female; Tumor Microenvironment; lidé středního věku; Middle Aged